Microalgae-bacterial biomass outperforms PN-anammox biomass for oxygen saving in continuous-flow granular reactors facing extremely low-strength freshwater aquaculture streams. (December 2022) - Santorio, Sergio; Val del Rio, Angeles; Amorim, Catarina L.; Couto, Ana T.; Arregui, Luz; Castro, Paula M.L.; Mosquera-Corral, Anuska
Abstract: The dissolved oxygen (DO) concentration in water streams is one of the most important and critical quality parameters in aquaculture farms. The main objective of this study was to evaluate the potential of two Continuous Flow Granular Reactors, one based on Partial Nitrification-Anammox biomass (Aquammox CFGR) and the other on Microalgae-Bacteria biomass (AquaMab CFGR), for improving dissolved oxygen availability in the recirculation aquaculture systems (RAS). Both reactors treated the extremely low-strength effluents from a freshwater trout farm (1.39 mg NH4 + -N/L and 7.7 mg TOC/L). The Aquammox CFGR, removed up to 68% and 100% of ammonium and nitrite, respectively, but the DO concentration in the effluent was below 1 mg O2 /L while the anammox activity was not maintained. In the AquaMab CFGR, bioaugmentation of aerobic granules with microalgae was attained, producing an effluent with DO concentrations up to 9 mg O2 /L and removed up to 77% and 80% of ammonium and nitrite, respectively, which is expected to reduce the aeration costs in fish farms. Graphical abstract: Image 1 Highlights: Microalgae-Bacteria granules greatly succeeded over PN-AMX granules. PN-AMX granules facing recirculating aquaculture effluents lost their anammox activity. Aerobic granules bioaugmentation with microalgae favoured the treatment process. Microalgae attachment to granules allowed their retention in the continuous flow system. Treated effluents meet the requirements for water recirculation in the aquaculture farm.